Chromosomal inversions and the reproductive isolation of species - Noor, Mohamed A. F. (The National Academy of Sciences, 2001)
Recent genetic studies have suggested that many genes contribute to differences between closely related species that prevent gene exchange, particularly hybrid male sterility and female species preferences. We have examined the genetic basis of hybrid sterility and female species preferences in Drosophila pseudoobscura and Drosophila persimilis, two occasionally hybridizing North American species. Contrary to findings in other species groups, very few regions of the genome were associated with these characters, and these regions are associated also with fixed arrangement differences (inversions) between these species. From our results, we propose a preliminary genic model whereby inversions may contribute to the speciation process, thereby explaining the abundance of arrangement differences between closely related species that co-occur geographically. We suggest that inversions create linkage groups that cause sterility to persist between hybridizing taxa. The maintenance of this sterility allows the species to persist in the face of gene flow longer than without such inversions, and natural selection will have a greater opportunity to decrease the frequency of interspecies matings.